A Toughening and Anti‐Counterfeiting Benzotriazole‐Based High‐Performance Polymer Film Driven by Appropriate Intermolecular Coordination Force. Issue 4 (25th January 2021) - Cao, Liang; Yang, Li; Xu, Yewei; Yin, Qiang; Huang, Ying; Chang, Guanjun
Abstract: It is of great significance to circumvent the inherent trade‐off between strength and extensibility for epoxy resins. Herein dynamic Cu‐benzotriazole cross‐links are incorporated, as the appropriate intermolecular coordination interaction, into high performance epoxy networks, and the resulting epoxy resins exhibits outstanding thermal stability and mechanical properties, their strength and extensibility are simultaneously improved. Additionally, local manipulation of coordination crosslinking confers the film with anti‐counterfeiting function. Abstract : Dynamic Cu‐benzotriazole cross‐links, as the appropriate intermolecular coordination interaction, were incorporated into high performance epoxy networks, and the strength and extensibility of the resulting epoxy resins were simultaneously improved. Additionally, local manipulation of coordination crosslinking confers the film with anti‐counterfeiting function.